(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Urgency of the work is determination of the action of preparations «Artificial tear»and «Restasis» in treatment of eye burns. Purpose. To investigate activity of enzymes in the tear fluid of patients with burns of the eyes. Material and methods. Clinical studies were made in 24 patients with burns of the eye. The control studies were made in 12 healthy persons. Complex therapy was given to 14 patients and included preparations of «Artificial tear» and «Restasis». Activity of acid phosphotase, succinate dehydrogenase, lactate dehydrogenase, glucose-6-phosphate dehydrogenase were determined in the tear fluid of patients. Results. In conditions of application of preparations «Artificial tear» andRestasis» metabolic disturbances are prevented considerably resulting in stabilization of the membraneous structures of the tissue of the anterior section of the eye. Conclusions. The use of preparations of «Artificial tear» and Restasis» promoted reduction in activity of acid phosphatase and Restasis» in the tear fluid of patients of the basic group, in relation to the group of comparison.